Quality of Life and Its Associated Factors in Patients with Chronic Kidney Disease Undergoing Hemodialysis - Ni Wayan Kesari Dharmapatni; Ida Ayu Suptika Strisanti; Ni Wayan Erviana Puspita Dewi (Indonesian Journal of Global Health Research, 2026)
The increasing prevalence of CKD has become a global concern. Moreover, hemodialysis is one of the therapies that patients must undergo for life, which significantly impacts their overall well-being. Of course, the process greatly affects the patient's quality of life. This study aimed to assess the quality of life and its associated factors in patients with CKD undergoing hemodialysis. The study used a descriptive analytic design with a cross-sectional approach. The respondents were all patients undergoing hemodialysis in the room, totalling 74 respondents. Data collection was carried out through a questionnaire, namely demographic data and KDQOL SF-36 that are valid and reliable. Data analysis used bivariate tests, namely chi-square. The results showed that half of the respondents had a good quality of life (55.4%). Age, gender, and number of comorbidities had a significant relationship with the quality of life of CKD patients undergoing hemodialysis (p-value < 0.05). Hence, the importance of a multidisciplinary approach in the management of hemodialysis patients that includes psychological and social interventions. By understanding the factors that influence quality of life, healthcare professionals can design more targeted and effective intervention programs to improve patients' overall well-being.